A non-destructive methodology for estimating leaf biomass in Morus alba and Platanus hispanica in the urban area of central-western Argentina. Issue 3 (3rd July 2019) - Vento, Bárbara; Moreno, Gabriela; Martinez-Carretero, Eduardo
ABSTRACT: Most allometric equations to estimate tree biomass have been established in a forest context. However, trees living in an urban environment and trees living in a forest one are confronted with very different constraints that have consequences, among others, on their morphology. It is thus necessary to establish specific allometric equations to estimate the biomass of urban trees. We here explore morphological parameters from two species of trees ( Morus alba L. and Platanus hispanica Mill. ex Münchh.), located in an arid urban environment in central-western Argentina, to develop a non-destructive methodology for estimating leaf biomass. Our results show that, for the studied urban trees, crown parameters are better estimators than the diameter at breast height, and allowed us to propose allometric equations using crown height for estimating their leaf biomass.